The Tuberculosis and COVID-19 coinfection: A report of two cases at a tertiary referral in Indonesia - Jamal Zaini; Muhamad Rizqy Fadhillah; Tina Reisa; Fathiyah Isbaniyah; Raden Rara Diah Handayani (Journal of Infection in Developing Countries)
COVID-19 cases are still rising globally in the middle of the tuberculosis epidemic. Several countries have reported TB-COVID-19 coinfection that could pose a double burden in the health care facilities in developing countries. We reported two pulmonary tuberculosis patients coinfected with COVID-19 with an overlapping clinical manifestation of tuberculosis and COVID-19 with a good prognosis at the end of COVID-19 treatment. This paper aims to discuss TB patients' susceptibility against SARS-COV-2 infection, the clinical profile of TB-COVID-19 coinfection, and the disease's prognosis. The clinician should be aware of both common disease symptoms that appear in a patient and should be confirmed and treat promptly.